RNA-Sequencing Analysis Reveals a Regulatory Role for Transcription Factor Fezf2 in the Mature Motor Cortex - Clare, Alison J.; Wicky, Hollie E.; Empson, Ruth M.; Hughes, Stephanie M. (Frontiers in Molecular Neuroscience, 2017)
Forebrain embryonic zinc finger (Fezf2) encodes a transcription factor essential for the specification of layer 5 projection neurons in the developing cerebral cortex. As with many developmental transcription factors, Fezf2 continues to be expressed into adulthood, suggesting it remains crucial to the maintenance of neuronal phenotypes. Despite the continued expression, a function has yet to be explored for Fezf2 in the projection neurons of the developed cortex. Here, we investigated the role of Fezf2 in mature neurons, using lentiviral-mediated delivery of a shRNA to conditionally knockdown the expression of Fezf2 in the mouse motor cortex (M1). RNA-sequencing analysis of Fezf2-reduced M1 revealed significant changes to the transcriptome, identifying a regulatory role for Fezf2 in the mature M1. Kyoto Encyclopedia Genes and Genomes (KEGG) pathway analyses of Fezf2-regulated genes indicated a role in neuronal signalling and plasticity, with significant enrichment of neuroactive ligand-receptor interaction, cell adhesion molecules and calcium signalling pathways. Gene Ontology analysis supported a functional role for Fezf2-regulated genes in neuronal transmission and additionally indicated an importance in the regulation of behaviour. Using the mammalian phenotype ontology database we identified a significant overrepresentation of Fezf2-regulated genes associated with specific behaviour phenotypes, including associative learning, social interaction, locomotor activation and hyperactivity. These roles were distinct from that of Fezf2-regulated genes identified in development, indicating a dynamic transition in Fezf2 function. Together our findings demonstrate a regulatory role for Fezf2 in the mature brain, with Fezf2-regulated genes having functional roles in sustaining normal neuronal and behavioural phenotypes. These results support the hypothesis that developmental transcription factors are important for maintaining neuron transcriptomes and that disruption of their expression could contribute to the progression of disease phenotypes.